Morphological and Cultural Variability among Exserohilum turcicum Isolates Causing Turcicum Leaf Blight Disease of Maize in Manipur - Sethy, Sujit Kumar; Nongmaithem, Nabakishor; Sinha, Bireswar; Singh, Kh. Ibohal; Singh, N. Okendro; Priyadarshini, Munmun (International Journal of Bio-resource and Stress Management, 2023)
This present experiment was conducted May–October, 2021 and April–October, 2022) in the Laboratory, Department of Plant Pathology, College of Agriculture, Central Agricultural University, Imphal, Manipur, India to study the different morphological and cultural characterizations of the pathogen, Exserohilum turcicum responsible for causing the Northern corn leaf blight (NCLB)/ Turcicum leaf blight (TLB) disease of maize. A total of 10 accessions were used for this experiment which were collected from different districts of Manipur. Based on the colony colour, they were classified as black, greyish-black and light greyish. Pigmentation was the same, i.e., black for all. Based on sporulation they were categorised as excellent, good and moderate. Different types of growth patterns were also observed from different types of accessions, i.e., flattened, slightly raised fluffy and raised cottony. The margins were recorded as regular and irregular. The range of fresh and dry weight, varied from 12.12 g–5.15 g and 1.61 g–0.82 g, respectively. Among six different types of media used to measure radial colony growth, maize leaf extract was found to be the highest and corn meal agar was the least. The growth rate for up to 7 days was observed and it was found that OQ689065 was considered as fastest-growing among all while, OQ689062 was considered as slowest. As per the length of the conidia, the maximum and minimum length was found to be 91.70 µm and 57.35 µm. Similarly, the maximum and minimum width was found to be 18.01 µm and 11.09 µm. The average septation of 10 accessions varied from 6.4 to 4.3. The statistical analyses performed during this study were found significant.